Morphology control and photoluminescence properties of Eu3+-activated Y4Al2O9 nanophosphors for solid state lighting applications. Issue 18 (17th April 2018) - Das, Antika; Saha, Subhajit; Panigrahi, Karamjyoti; Mitra, Anuradha; Chatterjee, Rituparna; Ghorai, Uttam Kumar; Das, Biswajit; Chattopadhyay, Kalyan Kumar
Abstract : Spherical Eu 3+ :Y4 Al2 O9 nanophosphors exhibit brilliant PL behavior with enhanced color purity and excited state lifetime. Abstract : Rare-earth activated highly luminescent nanomaterials have become a pivotal cornerstone in solid state lighting, as well as in field emission display applications, due to their top-notch optical properties. In this work, Eu 3+ -doped Y4 Al2 O9 nanophosphors have been prepared by facile solvothermal reaction, with an average particle size of 32–45 nm. To achieve superior brightness, the surface morphology of the synthesized nanophosphors has been investigated in detail focusing on the variation of the solvothermal reaction duration and concentration of the capping agent (PEG) and a plausible growth mechanism is also discussed. The prepared nanophosphors are crystalline in nature and exhibit strong hypersensitive red emission under 394 nm UV excitation. Moreover, those nanophosphors not only show uniform emission over a large area but also demonstrate a high degree of excited state lifetime. The colour purity of the obtained red emission is also very high (92%). All of these properties strongly validate the bright prospect of this nanophosphor for use in solid state lighting applications.